UJI BEBERAPA KONSENTRASI TEPUNG DAUN GAMAL (Gliricidia sepium Jacq.) TERHADAP HAMA Sitophilus zeamais M. PADA BIJI JAGUNG DI PENYIMPANAN - Yulia ningsih; Desita Salbiah; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Corn grain in storage can be damaged by maize weevil Sitophilus zeamais M. pest. If corn grain stored juring 6 monts cause damage to reach 85%. The research aims to find a concentration of gamal leaf powder that cause mortality of maize weevil S. zeamais M. pest highest at corn grain in storage. Research has been conducted at the Laboratory of Plant Pests Faculty of Agriculture University of Riau from October until December 2015. The research was designed a completely randomized design (CRD) consisting of 5 treatments and 4 replications. The treatments tested were giving some concentration of gamal leaf powder are 0 g / 100 g of corn grain, 2 g / 100 g of corn grain, 4 g / 100 g of corn grain, 6 g / 100 g of corn grain, and 8 g / 100 g of corn grain. Data were analyzed statistically by analysis of variance and least significant difference test at the advanced level of 5%. The result showed that concentration of 8 g/ 100 g of corn grain can cause mortality of maize weevil S. zeamais M. pest highest at corn grain in storage with the early time of death at 44,25 hours after application, lethal time 50 of 279,50 hours after application and total mortality is 70%.Keyword: Gliricidia sepium Jacq., Sitophilus zeamais M., corn grain.